An immunological study of the structural relationship between ovine adrenal cytochromes P-450 - Louw, Ralie P.(Ralie Petronella) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1991.